1983
DOI: 10.1111/j.1432-1033.1983.tb07164.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Protonation Sites in Thermospermine and in Some Other Polyamines by 15N and 13C Nuclear Magnetic Resonance Spectroscopy

Abstract: The pK values of thermospermine, a novel asymmetric tetraamine (4,8-diazadodecane-l,12-diamine), have been determined for the first time by the conventional titration method with subsequent data analyses. It was found to be the most basic polyamine among naturally occurring tetraamines. The I5N N M R titration method was applied to determine its protonation site. Natural-abundance I5N magnetic resonance spectra of the polyamine have been recorded as a function of pH from its free to the protonated form. Its ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 43 publications
4
68
0
1
Order By: Relevance
“…This original phenol extraction, although variously modified for nowadays use [27], consistently precipitates the spermine as sperminediium (terminal NH3 + ) di(phenolate) at pH 7.9-8.0 [27], since the pKa value of phenol is 9.97 [potentiometric titration in H2O, 25 °C, ionic strength (NaCl) 0.1] [28], and the four pKa values of spermine are: pKa1 = 10.86 (terminal [29] NH3 + ), pKa2 = 10.05 (terminal NH3 + ), pKa3 = 8.82 (inner [29] NH2 + ), pKa4 = 7.95 (inner NH2 + ) [potentiometric titration in H2O, 25 °C, ionic strength (NaCl) 0.1] [30]. The cyclo-O8-Na + could react with alkaline (pH 7.9-8.0) buffered phenol [27] to disodium rhodizonate (C6Na2O6), a known [31] oxidation product of p-benzoquinone, which in turn is an oxidation product of phenol [32].…”
Section: Discussionmentioning
confidence: 99%
“…This original phenol extraction, although variously modified for nowadays use [27], consistently precipitates the spermine as sperminediium (terminal NH3 + ) di(phenolate) at pH 7.9-8.0 [27], since the pKa value of phenol is 9.97 [potentiometric titration in H2O, 25 °C, ionic strength (NaCl) 0.1] [28], and the four pKa values of spermine are: pKa1 = 10.86 (terminal [29] NH3 + ), pKa2 = 10.05 (terminal NH3 + ), pKa3 = 8.82 (inner [29] NH2 + ), pKa4 = 7.95 (inner NH2 + ) [potentiometric titration in H2O, 25 °C, ionic strength (NaCl) 0.1] [30]. The cyclo-O8-Na + could react with alkaline (pH 7.9-8.0) buffered phenol [27] to disodium rhodizonate (C6Na2O6), a known [31] oxidation product of p-benzoquinone, which in turn is an oxidation product of phenol [32].…”
Section: Discussionmentioning
confidence: 99%
“…Many nitrogen-containing natural products are aliphatic amines, which usually are protonated under physiological conditions and are, therefore, thought of as cationic species. Polyamines are usually considered to be polycationic; based on the published pK values, spermine (1) 1,2 will be 77-81% tetraprotonated and 19-23% triprotonated at physiological pH. Since it is entirely possible that some of the physiology of spermine is elicited by the triprotonated species, this raises the interesting question of its nature.…”
Section: Introductionmentioning
confidence: 98%
“…Since it is entirely possible that some of the physiology of spermine is elicited by the triprotonated species, this raises the interesting question of its nature. Using NMR methods, it has been concluded that in spermine the secondary (internal) amino groups are protonated last 1 and, therefore, the triprotonated species must have an unprotonated (neutral) secondary amino group. Superficially this seems contrary to expectation since, based on inductive contribution, secondary amines should be more basic than their primary analogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bacterial systems, tetraamines protect membranes against osmotic lysis. The physiochemical characteristics of the polyamines support macromolecular interactions with various modes of complex formation and various formation constants (19). These interactions are affected kinetically by small changes in the microenvironment.…”
mentioning
confidence: 99%